Transfer in the use of intensifiers - Lovrović, Leonarda (Vestnik za tuje jezike, 2019)
This paper investigates transfer in the use of English intensifiers by Croatian students of English. Since transfer is an important factor in second language acquisition and is very common in dif-ferent areas of language use, it has been the subject of various studies. In this paper, we focus on lexical transfer investigating its effects on the use of intensifiers among first-year undergraduate university students of English at Zadar University, Croatia. The aim of this cross-sectional study is to examine whether there is a connection between the use of intensifiers in L2 and L1, i.e. whether the knowledge of intensifiers in L1 Croatian influences learners' use or knowledge of intensifiers in L2 English. Intensity is a basic human cognitive category and has an important function in communication. Specifically, the speaker expresses emotions or an attitude towards a topic using intensifiers. Furthermore, intensifiers are used in different collocations modifying adjectives, ad-verbs, and verbs. However, this study focuses only on intensifiers that appear in adverb-adjective collocations, and their use is observed in a relatively large group of language learners at a single point in time. Relevant data are collected using questionnaires as well as cloze-tests and translation tasks which focus on semantics and collocation.
Keywords: angleščina; hrvaščina; Hrvaška; izražanje jakosti; prislov; študenti; transfer; tuji jeziki